Trends and Factors Related to Smokeless Tobacco Use in the United States - Chang, Joanne T. (Nicotine Tob Res, 2016)
BACKGROUND: While declines in smoking prevalence in the United States have been well documented, trends in smokeless tobacco (SLT) use are less clear. This study updates previous analyses of US SLT use prevalence to better understand trends and factors related to SLT use. METHODS: We used the Tobacco Use Supplement of the Current Population Survey (TUS-CPS) to examine trends and factors related to SLT use using joinpoint and logistic regression models. SLT consumption from 1985 to 2011 was obtained from the 2011 Federal Trade Commission Smokeless Tobacco Report. Sensitivity analyses were conducted for assessing the impact of varying frequency definitions of SLT use. RESULTS: Decreasing trends in smoking and SLT prevalence overall were observed from 1992 to 2003 independently of use definition. SLT prevalence in the total adult population significantly decreased at an annual percent change (APC) of 4.5% per year from 1992 to 2003, but has been approximately constant ever since. Similar patterns were also found in adult males (APC = −4.4%) and young males (APC = −9.5%). SLT per capita consumption decreased significantly from 1991 to 1999 (APC = −2.2%), but has since decreased at only 0.35% per year (1999–2011). SLT use was found to be associated with former smoker status, younger age, white race, living in rural areas, residence in the South, lower education and unemployment, adjusting for other factors. CONCLUSIONS: Declines in SLT use were found in the United States, suggesting tobacco control has had positive impacts, but these have slowed since 2003. Targeting tobacco control policies to at-risk demographic groups is needed to further reduce SLT use in the United States. IMPLICATIONS: This study confirms that the declines in SLT use prevalence stopped in 2003 across different demographic groups, consistent with trends in SLT consumption. In addition, the longer period of analysis in comparison with earlier studies allows for quantitative characterization of SLT use trends using joinpoint regression. The study also shows the impact of different SLT use definitions in determining tobacco product use prevalence and trends.